Haiti : Staff Report for the 1999 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This 1999 Article IV Consultation highlights that progress on structural reforms in Haiti in FY1998/99 has been mixed. In the financial sector, the central bank's supervisory capacity and the regulatory framework continued to be strengthened. Performance under the FY1997/98 Staff-Monitored Program (year ending in September) was satisfactory. As a result of firm policy implementation, inflation was reduced, the external current account deficit narrowed, and official net international reserves rose. Output growth picked up to about 3 percent. Credit policy was tighter than programmed, although the fiscal deficit was slightly higher than in the program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet